Cover feature: Development of an imaged capillary isoelectric focusing method for characterizing the surface charge of mRNA lipid nanoparticle vaccines. Issue 18 (2nd September 2019) - Loughney, John W.; Minsker, Kevin; Ha, Sha; Rustandi, Richard R.
Abstract : DOI:10.1002/elps.201900063 The cover picture shows a cut away image of a Lipid Nanoparticle (LNP) containing mRNA along with the cIEF profile of an mRNA‐LNP. A pI shift and generation of acidic variants is observed when exposed to higher temperatures.